Political animal : representing dogs in modern Russian culture - Mondry, Henrietta (Studies in Slavic literature and poetics, 2015)
"Focusing on the correlation between humans and dogs in traditional belief systems and cultural productions, this book shows that the dog incorporates various often-paradoxical meanings - moral, social and philosophical. This study contributes to the unfolding cultural history of human-animal relations across cultures."--